Redefining the roles of master and apprentice: Crossing the threshold through the co-creation of a first-year seminar - Kiester, Elizabeth; Holowko, Joseph (International Journal for Students as Partners, 2020)
Students as Partners is an innovative approach to higher education that seeks to redefine both student and faculty roles and expectations on college campuses through the creation of equitable and inclusive partnerships in a variety of ways. This paper details our research in the co-creation of the curriculum for an undergraduate first-year seminar. It describes our journey from conceptualization to assessment of the course including creating the class, administering it for first-year students in the fall of 2018, and evaluating how successful the course was based on both our own perspectives, as well as student course feedback. Findings suggest that both partners had a transformative experience in which they crossed a threshold, creating new expectations surrounding roles and relationships for future student-faculty partnerships. Additionally, the students enrolled in the course provided feedback about the perceived successfulness of the co-created curriculum and the overall course experience based on our collaborative efforts.